Predicting butyrate- and propionate-forming bacteria of gut microbiota from sequencing data. (31st December 2022) - Kircher, Berenike; Woltemate, Sabrina; Gutzki, Frank; Schlüter, Dirk; Geffers, Robert; Bähre, Heike; Vital, Marius
ABSTRACT: The bacteria-derived short-chain fatty acids (SCFAs) butyrate and propionate play important (distinct) roles in health and disease, and understanding the ecology of respective bacteria on a community-wide level is a top priority in microbiome research. Applying sequence data (metagenomics and 16S rRNA gene) to predict SCFAs production in vitro and in vivo, a clear split between butyrate- and propionate-forming bacteria was detected with only very few taxa exhibiting pathways for the production of both SCFAs. After in vitro growth of fecal communities from distinct donors (n = 8) on different substrates (n = 7), abundances of bacteria exhibiting pathways correlated with respective SCFA concentrations, in particular in the case of butyrate. For propionate, correlations were weaker, indicating that its production is less imprinted into the core metabolism compared with butyrate-forming bacteria. Longitudinal measurements in vivo (n = 5 time-points from 20 subjects) also revealed a correlation between abundances of pathway-carrying bacteria and concentrations of the two SCFAs. Additionally, lower bacterial cell concentrations, together with higher stool moisture, promoted overall bacterial activity (measured by flow cytometry and coverage patterns of metagenome-assembled genomes) that led to elevated SCFA concentrations with over-proportional levels of butyrate. Predictions on pathway abundances based on 16S rRNA gene data using our in-house database worked well, yielding similar results as metagenomic-based analyses. Our study indicates that stimulating growth of butyrate- and propionate-producing bacteria directly leads to more production of those compounds, which is governed by two functionally distinct bacterial groups facilitating the development of precision intervention strategies targeting either metabolite.